1999
DOI: 10.1177/096368979900800102
|View full text |Cite
|
Sign up to set email alerts
|

Article Commentary: Transplants of Neuronal Cells Bioengineered to Synthesize GABA Alleviate Chronic Neuropathic Pain

Abstract: The use of cell lines utilized as biologic "minipumps" to provide antinociceptive molecules, such as GABA, in animal models of pain is a newly developing area in transplantation biology. The neuronal cell line, RN33B, derived from E13 brain stem raphe and immortalized with the SV40 temperature-sensitive allele of large T antigen (tsTag), was transfected with rat GAD67 cDNA (glutamate decarboxylase, the synthetic enzyme for GABA), and the GABAergic cell line, 33G10.17, was isolated. The 33G10.17 cells transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 74 publications
5
77
0
Order By: Relevance
“…light touch). Moreover, intrathecal administration of GABA, GABA A , or GABA B receptor agonists following peripheral nerve injury has been shown to reduce neuropathic pain (Eaton et al, 1999a(Eaton et al, , 1999bAsiedu et al, 2010;Munro et al, 2010). Thus, there is adequate evidence to suggest that hyperalgesia and allodynia after nerve injury are a result of impaired inhibitory neurotransmission and/or dysfunctional GABA-ergic inter-neurons in the dorsal horn of the spinal cord (Moore et al, 2002).…”
Section: Gaba-ergic Cell Therapy For Relieving Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…light touch). Moreover, intrathecal administration of GABA, GABA A , or GABA B receptor agonists following peripheral nerve injury has been shown to reduce neuropathic pain (Eaton et al, 1999a(Eaton et al, , 1999bAsiedu et al, 2010;Munro et al, 2010). Thus, there is adequate evidence to suggest that hyperalgesia and allodynia after nerve injury are a result of impaired inhibitory neurotransmission and/or dysfunctional GABA-ergic inter-neurons in the dorsal horn of the spinal cord (Moore et al, 2002).…”
Section: Gaba-ergic Cell Therapy For Relieving Neuropathic Painmentioning
confidence: 99%
“…However, systemic administration of GABA-enhancing drugs is not efficacious for relieving neuropathic pain, as it cannot specifically improve inhibitory neurotransmission in the spinal cord and is associated with significant side effects. Therefore, the idea of grafting of GABA-secreting cells or GABA-ergic neurons directly into the spinal cord has received considerable interest in neuropathic pain models (Eaton et al, 1999a(Eaton et al, , 1999b(Eaton et al, , 2007Mukhida et al, 2007).…”
Section: Gaba-ergic Cell Therapy For Relieving Neuropathic Painmentioning
confidence: 99%
“…Similarly, several studies have shown that intrathecal galanin significantly reduces allodynia induced by chronic constriction injury (6,34,35). In addition, Eaton et al (36) have shown that a spinal cord implant of genetically modified cells that secrete galanin significantly reduces allodynia after chronic constriction injury.…”
mentioning
confidence: 94%
“…the subarachnoid space shows an improvement of pain-like responses induced by injury to the peripheral nerve [14,15]. A subarachnoid transplant of the carcinoma-derived neuronal cell line that secretes GABA attenuates pain-like responses following SCI [16].…”
Section: Introductionmentioning
confidence: 99%